A study on the business marketing department of Telekom Malaysia Berhad (Kuching Division) / Suhardi Sahari - Sahari, Suhardi (1992)
Telekom Malaysia Bhd is a monopoly in providing telecommunication network. Ever since its privatization, it has undergone much changes especially in its—bit toward becoming a business culture. An apparent change can be seen through the formation of the Marketing Unit which comprises the Business Marketing Department and the Residential Marketing Department. This study which covers basically the Business Marketing Department of Telekom Malaysia Bhd, Kuching, Sarawak, is to look into the problems faced by the department. Two sets of questionnaires, were distributed to the business marketing staffs and the business customers respectively. Lacking of product knowledge and marketing ability is the major problems faced by the business marketing staffs. Shortage of manpower seemed to be the additional burden to the department. Therefore, with such situation, it is rather difficult for the department and Telekom Malaysia, Kuching as a whole to be a strong and effective marketing organization